Development of an Automated, High-Throughput Bactericidal Assay That Measures Cellular Respiration as a Survival Readout for Neisseria meningitidis - Mak, Puiying A. (American Society for Microbiology, 2011)
Complement-mediated bactericidal activity has long been regarded as the serological correlate of protective immunity against Neisseria meningitidis. This was affirmed in 2005 at a WHO-sponsored meningococcal serology standardization workshop. The assay currently employed by most laboratories involves determining surviving bacterial colony counts on agar as a readout which is labor-intensive, time-consuming, and not amendable to rapid data analysis for clinical trials. Consequently, there is an acute need to develop a sensitive, high-throughput bactericidal assay to enable a rapid and robust assessment of the effectiveness of vaccine candidates. To this end, we have developed an automated, kinetic assay based on the fluorescent respiration product of resazurin which reduces assay volume, shortens assay time, and facilitates automation of data analysis. We demonstrate proof of concept for applicability of this high-throughput system with multiple meningococcal strains and utilizing different lots of human complement. The assay is robust and highly reproducible. Titers obtained by the fluorescence readout method are strongly correlated with the data obtained using the conventional, agar plate-based assay. These results demonstrate that the detection of bacteria that have survived the bactericidal reaction by measuring metabolic activity using a fluorescent dye as an alternative readout is a promising approach for the development of a high-throughput bactericidal assay.